Analysis of Employee Discipline at Favehotel Pgc Cililitan - Hanifah Septika; Christian Wiradendi Wolor; Suherdi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze the level of employee discipline at Favehotel PGC Cililitan, especially related to employee attendance. This research uses a qualitative descriptive method with a case study approach. Data was collected through interviews with four participants from various divisions, direct observation, and related documentation. The results showed that Favehotel PGC Cililitan has implemented an effective fingerprint attendance system, but sometimes experiences technical problems. Employees of Favehotel PGC Cililitan show a good level of work discipline, especially in terms of punctuality, utilization of facilities, and adherence to work standards. Factors such as sudden meetings, health conditions, traffic congestion, and public transportation constraints can be obstacles in maintaining punctuality. Favehotel PGC Cililitan applies graduated sanctions, ranging from verbal reprimands to written warnings to address lateness issues and encourage positive behavioral changes. This research provides valuable insights into the factors that influence employee work discipline in the company and provides recommendations for further improvement including improved communication between employees and management, as well as training and development to improve employee competencies.